Epstein–Barr Virus Induces Adipocyte Dedifferentiation to Modulate the Tumor Microenvironment - Liu, Shu-Chen; Tsang, Ngan-Ming; Lee, Po-Ju; Sui, Yun-Hua; Huang, Chen-Han; Liu, Tzu-Tung (Cancer research (Chicago, Ill.), 2021)
The most frequent location of metastatic EBV+ nasopharyngeal carcinoma (NPC) is the bone marrow, an adipocyte-dominant region. Several EBV-associated lymphoepithelioma-like carcinoma (LELC) types also grow in the anatomical vicinity of fat tissues. Here we show that in an adipose tissue-rich tumor setting, EBV targets adipocytes and remodels the tumor microenvironment. Positive immunoreactivity for EBV-encoded early antigen D was detected in adipose tissue near tumor beds of bone marrow metastatic NPC. EBV was capable of infecting primary human adipocytes , triggering expression of multiple EBV-encoded mRNA and proteins. In infected adipocytes, lipolysis was stimulated through enhanced expression of lipases and the AMPK metabolic pathway. The EBV-mediated imbalance in energy homeostasis was further confirmed by increased release of free fatty acids, glycerol, and expression of proinflammatory adipokines. Clinically, enhanced serum levels of free fatty acids in patients with NPC correlated with poorer recurrence-free survival. EBV-induced delipidation stimulated dedifferentiation of adipocytes into fibroblast-like cells expressing higher levels of S100A4, a marker protein of cancer-associated fibroblasts (CAF). IHC analyses of bone marrow metastatic NPC and salivary LELC revealed similar structural changes of dedifferentiated adipocytes located at the boundaries of EBV+ tumors. S100A4 expression in adipose tissues near tumor beds correlated with fibrotic response, implying that CAFs in the tumor microenvironment are partially derived from EBV-induced dedifferentiated adipocytes. Our data suggest that adipose tissue serves as an EBV reservoir, where EBV orchestrates the interactions between adipose tissues and tumor cells by rearranging metabolic pathways to benefit virus persistence and to promote a protumorigenic microenvironment. SIGNIFICANCE: This study suggests that Epstein-Barr virus hijacks adipocyte lipid metabolism to create a tumor-promoting microenvironment from which reactivation and relapse of infection could potentially occur.